2014
DOI: 10.1016/j.bbamem.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Induced movements of giant vesicles by millimeter wave radiation

Abstract: Our previous study of interaction between low intensity radiation at 53.37GHz and cell-size system - such as giant vesicles - indicated that a vectorial movement of vesicles was induced. This effect among others, i.e. elongation, induced diffusion of fluorescent dye di-8-ANEPPS, and increased attractions between vesicles was attributed to the action of the field on charged and dipolar residues located at the membrane-water interface. In an attempt to improve the understanding on how millimeter wave radiation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Where responses are observed (Ramundo-Orlando and Gallerano 2009), some appear to be associated with temperature increases (Wilmink et al 2011), but others seem to be caused by direct, temperature-independent interactions of electric fields with biological processes (Titova et al 2013a; Titova et al 2013b). Millimeter waves, an electromagnetic regime that may be considered to overlap with terahertz radiation, have also been reported to affect biological systems (Ramundo-Orlando et al 2007; Kim et al 2013; Albini et al 2014; Romanenko et al 2014), and these phenomena may be related. Because effects from both picosecond pulses and terahertz radiation imply electric-field-driven biomolecular rearrangements on the picosecond time scale, the mechanisms for the two sets of phenomena are likely to be related, and it may be beneficial to consider them together.…”
Section: Introductionmentioning
confidence: 99%
“…Where responses are observed (Ramundo-Orlando and Gallerano 2009), some appear to be associated with temperature increases (Wilmink et al 2011), but others seem to be caused by direct, temperature-independent interactions of electric fields with biological processes (Titova et al 2013a; Titova et al 2013b). Millimeter waves, an electromagnetic regime that may be considered to overlap with terahertz radiation, have also been reported to affect biological systems (Ramundo-Orlando et al 2007; Kim et al 2013; Albini et al 2014; Romanenko et al 2014), and these phenomena may be related. Because effects from both picosecond pulses and terahertz radiation imply electric-field-driven biomolecular rearrangements on the picosecond time scale, the mechanisms for the two sets of phenomena are likely to be related, and it may be beneficial to consider them together.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of MMW on neurons is a result of coupling with another membrane-related mechanism. Studies by Ramundo-Orlando et al [ 70 , 78 81 ] showed increased permeability in membranes of artificial liposomes upon the application MMW–terahertz radiation. Membranes loaded with carbonic anhydrase liposomes subjected to 53.37 GHz 0.1 mW cm −2 radiation exhibited an enhanced carbonic anhydrase reaction rate when p -nitrophenyl acetate was applied [ 79 , 82 ].…”
Section: Biological Effects Of Millimetre Wavementioning
confidence: 99%